Clinical dilemmas in viral liver disease - 4 0 16; Foster, Graham R.,;Reddy, K. Rajender; 5 (Hoboken, NJ, USA : Wiley-Blackwell, 2020)
Viral hepatitis is an extremely complex disease to treat. The medical team involved in the care of patients with viral hepatitis will be faced on a daily basis with clinical challenges. The answers to specific questions are not easily located in the current medical literature: if they are there, they may only be found after extensive searching or the compilation of information from numerous sources. The aim of this book is to provide evidence-based guidance on topical clinical questions and difficulties/dilemmas encountered by the medical team involved in the diagnosis, treatment and management of patients with viral liver disease: the medical team includes the hepatologist/pediatric hepatologist, pathologist, radiologist, transplant surgeon and nurse specialist. This book presents specific and clearly defined topics, in short chapters, selected either because they are of interest in themselves, recent developments or areas of controversy.It will be of particular interest to trainees and fellows in hepatology--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; diagnosis;therapy;diagnosis;therapy;diagnosis;therapy -- Hepatitis, Viral, Human;Hepatitis, Viral, Human;Hepatitis, Chronic;Hepatitis, Chronic;Liver Cirrhosis;Liver Cirrhosis;Diagnostic Techniques, Digestive System -- 20; 20; 2